Licchavi saṃvatko paricarca - Rājavaṃśī, Śaṅkaramāna (Girīndramāna Rājavaṃśī, 1989)
On the Licchavi era of ancient Nepal.
In Nepali.
On the Licchavi era of ancient Nepal.
Keywords: Nepal / History / Licchavi dynasty, ca. 400-600